Candida auris otomycosis in Iran and review of recent literature. Issue 2 (28th January 2019) - Abastabar, Mahdi; Haghani, Iman; Ahangarkani, Fatemeh; Rezai, Mohammad Sadegh; Taghizadeh Armaki, Mojtaba; Roodgari, Somayeh; Kiakojuri, Keyvan; Al‐Hatmi, Abdullah M. S.; Meis, Jacques F.; Badali, Hamid
Summary: Candida auris is a multidrug‐resistant yeast emerging in immunocompromised and in otherwise healthy individuals. Due to difficulties in microbiological identification of C. auris because of the lack of available laboratory technology in developing countries, the number of patients affected is most likely underestimated. We report the first case of C. auris otitis which now adds Iran as the fifth country around the Persian Gulf, in addition to Kuwait, Oman, United Arab Emirates and Saudi Arabia. Candida auris is an unknown pathogen in routine laboratories in Iran because most Candida isolates are probably misdiagnosed. Otomycosis seems to be a different clinical presentation of C. auris mainly involving isolates from the East‐Asian clade. We compared the mycological and clinical details of the Iranian patient with other cases of otitis reported since the last review of C. auris otomycosis in 2017.